Knowledge, attitude and practice of medical and health sciences students at IIUM towards Zika virus - Mohammed Ahmed, Abdul Kareem; Jamshed, Shazia Qasim; Elsayed, Tarek Mohamed Ali; Elkalmi, Ramadan Mohamed Mahmod (Malaysian Pharmaceutical Society, 2017)
Zika virus is a mosquito-borne flavivirus that was first identified in Uganda in 1947. The most common complications of this virus are congenital brain abnormalities to the foetus and Guillain-Barré syndrome in the infected person. This study aims to assess knowledge, attitude and practice towards Zika virus among undergraduate medical and health science students at International Islamic University Malaysia (IIUM). The study is a cross-sectional and involved 180 final year students from Kulliyyah of Pharmacy and Kulliyyah of Allied Health Sciences and third and fourth year students from Kulliyyah of Dentistry and Kulliyyah of Medicine. A self-administered questionnaire was used for data collection. Data were transferred to and analysed using the Statistical Package for Social Software (SPSS). A response rate of the study was 85.5% (171/200), with 57 (33.33%) males and 114 (66.67%) females was observed. The knowledge of the students of the cause, signs and symptoms of Zika virus was quite good, but moderate regarding the complications of Zika virus. A majority of them had a common perspective that baby will be the most affected from Zika virus indicating that they had a good knowledge toward Zika virus. Lastly, approximately half of them were considering taking preventative measure against Zika virus. This study revealed that these students have a moderate level of knowledge and practice towards Zika virus. But, in terms of attitude, they have a good attitude towards it. Thus, further exposure is needed and students are expected to be acclimatized towards more details about the harmful effect of Zika in humans. Knowledge about Zika was the most crucial part as zero knowledge about Zika could contribute to poor attitude and practice towards the disease itself and at the end will cause harm to human beings.